Saponins from the roots of Chenopodium bonus-henricus L. with neuroprotective and anti-α-glucosidase activities - Zlatina Kokanova-Nedialkova; Magdalena Kondeva-Burdina; Paraskev Nedialkov (Pensoft Publishers, 2021)
Six saponins of phytolaccagenin, bayogenin, medicagenic acid, 2β-hydroxygypsogenin, and 2β-hydroxyoleanoic acid from the roots of Chenopodium bonus-henricus L. were investigated for neuroprotective and anti-α-glucosidase activities. All tested saponins (10 µM) showed statistically significant neuroprotective activities on isolated rat brain synaptosomes using a 6-hydroxydopamine in vitro model. They preserved synaptosome viability as well as the reduced glutathione level. The bayogenin glycoside (Chbhs-05) possessed the most prominent neuroprotective effect. The anti-α-glucosidase activity of the tested saponins was established by measuring the levels of the released 4-nitrophenol using LC-MS. Bonushenricoside B (Chbhs-07) showed the highest inhibitory effect against α-glucosidase (44.1%) compared to the positive control acarbose (36.3%) at a concentration of 625 µM.